1997
DOI: 10.1002/(sici)1099-1026(199703)12:2<63::aid-ffj614>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Analyses of Enantiomers of Essential Oils from Madagascar

Abstract: The volatile constituents of twelve essential oils from Madagascar, namely those of Cinnamomum camphora (L.) Presl, Cinnamomum zeylanicum Blume (leaf oil), Hedychium¯avum Roxb., Helichrysum gymnocephalum Humbert, Helichrysum selaginifolium L., Lantana camara L., Pelargonium roseum Willd., Piper nigrum L., Ravensara aromatica Havozo (bark oil and leaf oil), Vetiveria zizanioides (L.) Nash ex Small and Zingiber ocinale Roscoe were identi®ed and quanti®ed by high resolution capillary gas chromatography coupled to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(30 citation statements)
references
References 7 publications
4
23
0
2
Order By: Relevance
“…10;2012 (3.22%), calarene (3.19%), ∆-cadinene (2.9%), α-pinene (2.11%) and trans-sabinene (1.09%). These results were in agreement with most published data like the South Chinese essential oil revealed by Sundufu and Shoushan (2004) where they found almost exact α-humulene (9.3%), higher 1,8-cineol (4.6%), lower sabinene (1.1%), lower α-pinene (0.8%), lower isomer β-caryophyllene (13.35%) and dominant higher germacrene D (15.9%) also higher germacrene D was found in other studies (da Silva et al, 1999;Möllenbeck et al, 1997). Recent study in Algeria reported that β-caryophyllene was dominant (35.7%) and lower α-humulene (3.72%), in L. camara oil (Zoubiri & Baaliouamer, 2011).…”
Section: Chemical Composition Of the Essential Oilsmentioning
confidence: 99%
“…10;2012 (3.22%), calarene (3.19%), ∆-cadinene (2.9%), α-pinene (2.11%) and trans-sabinene (1.09%). These results were in agreement with most published data like the South Chinese essential oil revealed by Sundufu and Shoushan (2004) where they found almost exact α-humulene (9.3%), higher 1,8-cineol (4.6%), lower sabinene (1.1%), lower α-pinene (0.8%), lower isomer β-caryophyllene (13.35%) and dominant higher germacrene D (15.9%) also higher germacrene D was found in other studies (da Silva et al, 1999;Möllenbeck et al, 1997). Recent study in Algeria reported that β-caryophyllene was dominant (35.7%) and lower α-humulene (3.72%), in L. camara oil (Zoubiri & Baaliouamer, 2011).…”
Section: Chemical Composition Of the Essential Oilsmentioning
confidence: 99%
“…Triterpenes (Lantadene type), steroids and alkaloids are reported as major phytochemical constituents of L. camara [9][10][11][12][13]. However, published reports on leaf essential oil compositions have reported the high content of sesquiterpenes with mainly β-caryophyllene [13][14][15], zingiberene, arcurcumene [15], gemacrene-D, bisabolene [16], δ-humulene [13,17] derivatives up to 65% as major essential oil constituents. Although several reports are available in literature concerning phytochemical investigations and biological activities of L. camara, reports on accumulation of secondary metabolites such as phenolics, flavonoids and proanthocyanidins in leaves and their antioxidant activities has not yet been studied sufficiently.…”
Section: Introductionmentioning
confidence: 99%
“…The oil with a high content of camphor has an important antifungal activity (Takaoka et al, 1976;Sattar et al, 1991). C. camphora has several chemical varieties which have different essential oil compositions (Hattori, 1981;Huergo et al, 1978;Lin et al, 1994;Akeng´a et al, 1994;Moellenbeck et al, 1997;Dung et al, 1993). Two varieties have been exploited commercially, Hon-Sho (C. camphora Nees & Eberm.…”
Section: Introductionmentioning
confidence: 99%